Broadband degenerate four-wave mixing of OH for flame thermometry - Lloyd, G; Hughes, I; Bratfalean, R; Ewart, P (1998)
Multiplex DFWM spectroscopy of OH using a broad-bandwidth modeless laser is reported. Temperatures are derived from single-shot and averaged multiplex spectra. The results are compared to those from DFWM spectra obtained using a scanning narrow linewidth laser. Systematic errors in derived temperatures arising from absorption are found to be smaller for multiplex spectra than scanning narrowband spectra at equivalent levels of saturation. The reduced sensitivity to absorption of broadband multiplex spectra is shown to be in agreement with results of a model of DFWM which includes non-degenerate contributions to the signal intensity. © Springer-Verlag 1998.